AN ANALYSIS OF DEVELOPING ENGLISH TEACHING MATERIALS AT THE VOCATIONAL HIGH SCHOOL IN CIMAHI - Acep Haryudin; Yana Yana; Efransyah Efransyah (IKIP Siliwangi Bandung, 2020)
The purpose of this study was to analyze the development of English teaching materials at the vocational high school (SMK) Mohammad Toha in Cimahi, the availability and suitability of English teaching materials to the needs of students, especially teaching materials / materials that students learn according to their level of needs in the world of work especially for SMK students. The research problem formulation is; 1) how is the development of English teaching materials used in vocational high school (SMK) Mohammad Toha Cimahi especially in computer and network engineering (TKJ) majors? 2) what difficulties did the teachers get in developing specific English language teaching materials ?. And the purpose of the study was to develop more specific English Language Teaching Materials in accordance with the field of vocational students at Mohammad Toha Cimahi Vocational School (SMK) especially in the Department of Computer and Network Engineering (TKJ). 2) To find solutions to the obstacles faced by teachers in developing specific English Language teaching materials. This research method uses descriptive qualitative method which aims to describe the development of English Language Teaching Materials in Vocational High Schools (SMK). The results and findings in the field that students have high motivation to learn English, but there are obstacles they face including; 1) The material presented still does not meet the target needs of students for their career world, 2) Authentic material is not yet available, 3) The absence of developers / innovations in the development of teaching environments conducted by schools and teachers so that the material presented still does not answer the needs of students in SMK, innovation has not been made in developing teaching materials at school so the material presented is still textual. Teachers experience difficulties in developing teaching materials because of the lack of knowledge, the absence of experts in the development of teaching materials and the lack of training and reference in the development of teaching materials.